2019
DOI: 10.1051/matecconf/201925403007
|View full text |Cite
|
Sign up to set email alerts
|

Road train motion stability in BRT system

Abstract: The peculiarities of organization and perspectives of mass passenger transportation in the city and beyond are considered with the use of "Bus Rapid Transport" (BRT) or Metrobus. Different aspects of study of motor vehicles (MV) controllability and stability are analyzed. It is substantiated that it is sufficient to consider the potential stability of the MV itself, in order to guarantee the stability of the "driver MV" system with a large reserve. A mathematical model of a three-axle bus train consisting of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
3
Order By: Relevance
“…To solve the problem of stability of rectilinear motion of a road train it is necessary to make a system of equations of its perturbed motion. This system allows to determine the reactions of the links of the road train in a single disturbance (a sharp turn of the steering In [14], a system of equations describing the plane-parallel motion of an articulated bus was obtained. This system is written as: • for the bus ; ;…”
Section: The Results Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…To solve the problem of stability of rectilinear motion of a road train it is necessary to make a system of equations of its perturbed motion. This system allows to determine the reactions of the links of the road train in a single disturbance (a sharp turn of the steering In [14], a system of equations describing the plane-parallel motion of an articulated bus was obtained. This system is written as: • for the bus ; ;…”
Section: The Results Of the Studymentioning
confidence: 99%
“…In [13][14][15] a complex method of choosing the parameters of a road train was developed, based on mathematical models of its rectilinear and controlled motion, taking into account the angles of installation of the axles of a tractor and a semi-trailer. It is shown that the movement of a road train, consisting of a two-axle tractor and a three-axle semi-trailer, without the skew axles, is asymptotically stable.…”
Section: Analysis Of Recent Researchmentioning
confidence: 99%
“…У роботі [8] отримано систему диференціальних рівнянь, що описує плоскопаралельний рух ланок триланкового шарнірно-зчленованого автобуса, рис. 1.…”
Section: результати дослідженняunclassified
“…De acordo com a Administração Federal de Trânsito (AFT), é um sistema de trânsito que pode incluir prioridade de semáforos, plataformas elevadas e estações melhoradas (V. Perk, Catalá, Mantius, & Corcoran, 2017). O consideram um sistema de tráfego de ônibus bastante complexo, porque envolve a circulação de ônibus em ônibus especialmente designados e, muitas vezes, em faixas de tráfego cercadas (Sakhno et al, 2019). Algumas das definições possíveis estão relacionadas ao seu desempenho e modo de operação como parte de um sistema de transporte público, conforme descrito em Dantas, Dantas, Melo, Maciel, and Alves (2018) considerando que o veículo percorre uma única rota entre um conjunto de estações, tendo como ponto de partida uma estação central e o destino do veículo como estação final (Dantas et al, 2021).…”
Section: Sistema De Trânsito Rápido De ôNibus (Brt)unclassified
“…Esse sistema se tornou uma solução de trânsito popular para cidades que desejam otimizar a mobilidade urbana e as oportunidades e eficiências econômicas por meio da melhoria do valor do solo e da propriedade (Zhang & Yen, 2020). Bem como um excelente auxiliar na resolução de problemas ecológicos e de transporte, com um curto tempo de implementação (Sakhno et al, 2019) (Kassens-Noor, Gaffney, Messina, & Phillips, 2018). No entanto, esses benefícios podem variar muito em uma área urbana para outra, dependendo das características da rede (Wirasinghe et al, 2013).…”
Section: Vantagensunclassified